Effect of semi-permeable cover system on the bacterial diversity during sewage sludge composting. (1st June 2018) - Robledo-Mahón, Tatiana; Aranda, Elisabet; Pesciaroli, Chiara; Rodríguez-Calvo, Alfonso; Silva-Castro, Gloria Andrea; González-López, Jesús; Calvo, Concepción
Abstract: Sewage sludge composting is a profitable process economically viable and environmentally friendly. In despite of there are several kind of composting types, the use of combined system of semipermeable cover film and aeration air-floor is widely developed at industrial scale. However, the knowledge of the linkages between microbial communities structure, enzyme activities and physico-chemical factors under these conditions it has been poorly explored. Thus, the aim of this study was to investigate the bacterial dynamic and community structure using next generation sequencing coupled to analyses of microbial enzymatic activity and culturable dependent techniques in a full-scale real composting plant. Sewage sludge composting process was conducted using a semi-permeable Gore-tex cover, in combination with an air-insufflation system. The highest values of enzymatic activities such as dehydrogenase, protease and arylsulphatase were detected in the first 5 days of composting; suggesting that during this period of time a greater degrading activity of organic matter took place. Culturable bacteria identified were in agreement with the bacteria found by massive sequencing technologies. The greatest bacterial diversity was detected between days 15 and 30, with Actinomycetales and Bacillales being the predominant orders at the beginning and end of the process. Bacillus was the most representative genus during all the process. A strong correlation between abiotic factors as total organic content and organic matter and enzymatic activities such as dehydrogenase, alkaline phosphatase, and ß-glucosidase activity was found. Bacterial diversity was strongly influenced by the stage of the process, community-structure change was concomitant with a temperature rise, rendering favorable conditions to stimulate microbial activity and facilitate the change in the microbial community linked to the degradation process. Moreover, results obtained confirmed that the use of semipermeable cover in the composting of sewage sludge allow a noticeable reduction in the process-time comparing to conventional open windrows. Graphical abstract: Image 1 Highlights: A microbial study on a full-scale sewage-sludge compost pile was performed. Actinomycetales and Bacillales were the most abundant orders during the process. Dehydrogenase and ß-glucosidase were correlated with the organic matter. Bacillus was the predominant genus isolated during all the stages of composting.